Obstructive Sleep Apnea, Obesity, and the Development of Acute Respiratory Distress Syndrome - Karnatovskaia, Lioudmila V. (American Academy of Sleep Medicine, 2014)
BACKGROUND: Obstructive sleep apnea (OSA) may increase the risk of respiratory complications and acute respiratory distress syndrome (ARDS) among surgical patients. OSA is more prevalent among obese individuals; obesity can predispose to ARDS. HYPOTHESIS: It is unclear whether OSA independently contributes towards the risk of ARDS among hospitalized patients. METHODS: This is a pre-planned retrospective subgroup analysis of the prospectively identified cohort of 5,584 patients across 22 hospitals with at least one risk factor for ARDS at the time of hospitalization from a trial by the US Critical Illness and Injury Trials Group designed to validate the Lung Injury Prediction Score. A total of 252 patients (4.5%) had a diagnosis of OSA at the time of hospitalization; of those, 66% were obese. Following multivariate adjustment in the logistic regression model, there was no significant relationship between OSA and development of ARDS (OR = 0.65, 95%CI = 0.32-1.22). However, body mass index (BMI) was associated with subsequent ARDS development (OR = 1.02, 95%CI = 1.00-1.04, p = 0.03). Neither OSA nor BMI affected mechanical ventilation requirement or mortality. CONCLUSIONS: Prior diagnosis of OSA did not independently affect development of ARDS among patients with at least one predisposing condition, nor the need for mechanical ventilation or hospital mortality. Obesity appeared to independently increase the risk of ARDS. CITATION: Karnatovskaia LV, Lee AS, Bender SP, Talmor D, Festic E. Obstructive sleep apnea, obesity, and the development of acute respiratory distress syndrome. J Clin Sleep Med 2014;10(6):657-662.